Post COVID-19 vaccination binding and neutralizing antibody with or without previous infection: An 18-month longitudinal study in Indonesia - Ardyanto, Tonang D.; Khariri, Khariri; Agus, Telly P.; Subandrio, Amin (Narra J, 2024)
Due to the persisting development of SARS-CoV-2 variants, studies on the kinetics, duration, and function of antibodies are essential for vaccine development and long-term immunity prediction. This longitudinal study examined post-vaccination antibody responses in people after receiving CoronaVac or ChAdOx1 vaccines with or without a history of SARS-CoV-2 infection. Conducted in Indonesia between August 2021 and May 2023, this study involved 121 participants divided into two groups based on the received vaccine types and monitored for 18 months post-second dose vaccination by assessing the binding antibody (BAb) level and neutralizing antibody (NAb) inhibition rate at six time points. The study also documented the participants’ age, gender, and body mass index (BMI). Before the first dose vaccination, 85 (70.25%) participants were reactive BAb (defined by BAb level ≥50 AU/mL) indicating a history of infection. In the CoronaVac group, only 53.1% were reactive BAb. However, 100% of participants were positive NAb (defined by NAb inhibition rate ≥30%), which indicates a past history of infection with low initial or rapidly decreasing BAb levels. In the ChAdOx1 group, 81,9% of participants were reactive, while only 54.2% were positive NAb, suggesting a recent infection with a high BAb level but a relatively low NAb inhibition rate. During the 18 months post-second dose vaccination, the BAb levels fluctuated. However, 100% of participants were positive NAb. No significant difference in antibody response was documented among participants with or without infection history. Also, no significant impact was presented by the factors of sex, age, and BMI. The findings highlight the crucial of the vaccine in public health and how vaccination strategies could be optimized effectively during and after the post-pandemic.